2000
DOI: 10.1007/s100670050158
|View full text |Cite
|
Sign up to set email alerts
|

Skin Score Decrease in Systemic Sclerosis Patients Treated with Intravenous Immunoglobulin - A Preliminary Report

Abstract: The aim of the study was to determine for the first time the response of systemic sclerosis (SSc) patients to treatment with intravenous immunoglobulin (IVIg). Three patients with progressive and rapidly deteriorating disease (mainly affecting the skin) were planned to receive six monthly courses of high-dose IVIg (2 g/kg). All had a thorough physical examination, clinical evaluation by the modified Rodnan total skin thickness score, and measurement of the titres of PM-Scl antibodies before and after the treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 27 publications
1
29
0
1
Order By: Relevance
“…Imatinib inhibits the synthesis of major ECM proteins and prevents the development of fibrosis in the mouse model of bleomycin-induced dermal and pulmonary fibrosis [98,99]. In rat model of hepatic fibrosis, dual suppression of PDGF and TGF-β with a combination of clinically comparable low doses of imatinib and ACEI exerted a significant inhibitory effect on ongoing liver fibrosis development [100].…”
Section: Imatinib Mesylate (Gleevec)mentioning
confidence: 98%
See 1 more Smart Citation
“…Imatinib inhibits the synthesis of major ECM proteins and prevents the development of fibrosis in the mouse model of bleomycin-induced dermal and pulmonary fibrosis [98,99]. In rat model of hepatic fibrosis, dual suppression of PDGF and TGF-β with a combination of clinically comparable low doses of imatinib and ACEI exerted a significant inhibitory effect on ongoing liver fibrosis development [100].…”
Section: Imatinib Mesylate (Gleevec)mentioning
confidence: 98%
“…IVIg has been used successfully in clinical trials, and its effectiveness and safety have been established for the treatment of various autoimmune conditions [105,106]. Levy et al [97,99] reported on a significant decrease in the modified objective Rodnan total skin thickness score in patients diagnosed with systemic sclerosis and treated with courses of high-dose IVIg (2 g/kg). Myelofibrosis secondary to lupus was clinically improved after IVIg administration [106]; we [107] reported the preventive effect of IVIg on skin fibrosis in tight-skin mice.…”
Section: Intravenous Immunoglobulinmentioning
confidence: 99%
“…В одной из них авторы анализируют ре зультаты лечения трех больных ССД с быстро прогрессиру ющим течением и преимущественным поражением кожи [19]. Ввиду отсутствия эффекта предшествующей терапии, было начато лечение ВВИГ, который вводился в высоких дозах (2г/кг) один раз в мес в течение 6 мес.…”
Section: Discussionunclassified
“…In 2000, three patients with rapidly progressive SSc, mainly affecting the skin, were treated with high-dose IVIG: All three patients exhibited a substantial improvement in skin thickness compared with baseline skin thickness. However, one patient received only three monthly courses after which he developed renal failure and later died of sepsis [77]. In 2004, an open-label study on ten patients with dcSSc and five subjects with lcSSc treated with monthly IVIG infusions found that the mean degree of skin involvement evaluated with the modified Rodnan skin score decreased by 35 % during the time of the study, while a significant improvement in patients' well-being and quality of life was identified by means of a decrease in the Health Assessment Questionnaire (HAQ) score.…”
Section: Management Of Systemic Scleroderma With Intravenous Immunoglmentioning
confidence: 97%